L’idée républicaine dans l’émigration antifasciste en exil - Éric Vial (Laboratoire Italien)
The antifascist emigration of the interwar period, which forms part of the political class of the Italian Republic, may seem little concerned by the institutional issue, whether this emigration is seen as unanimous Republican or it is considered preferable to silence the possible differences. Yet the debate exists, even if it is rudimentary and often instrumentalized, as the reformist socialists were under the illusion that they could find support from monarchist liberals or even from the Crown. The controversy agitate the Italian Human Rights Leagueand the Anti-Fascist Concentration before dying in the late 1920s with an overall republicanization, that the attempt to broadest national unity, wanted by the Communist party in the time of the Popular fronts, disturbed only temporarily, as it was contrary to the identity of the parties, including this party, to the militants’ opinion, and to the influence of republican France as principal place of political emigration.